2014
DOI: 10.2478/mmr-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Three Different Modes of Femoral Hamstring Graft Fixation in Anterior Cruciate Ligament Reconstruction

Abstract: Introduction. There are various methods of anterior cruciate ligament (ACL) reconstruction of which the two main choices in autograft reconstruction involve the use of the bone-patella tendon-bone or hamstring graft. Femoral fixation can be divided into three main types: cortical suspensory devices such as Endobutton (Smith & Nephew, Arthrex), interference screws, and femoral transfixation devices such as Transfix (Arthrex) and Rigidfix (Depuy-Mitek). The aim of this study was to compare the clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 18 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Only two studies [6, 8] were not considered at risk of bias (Table 3). One study was an RCT [6], seven studies had a prospective design [8, 42, 43, 49, 54, 72, 75] and 14 assessed patients retrospectively [9, 12, 18, 20, 22, 26, 33, 38, 39, 41, 44, 45, 57, 62]. Arthroscopy and/or arthrotomy was used as a gold standard in 17 studies [6, 8, 9, 11, 12, 18, 20, 22, 25, 38, 39, 43, 44, 54, 57, 62, 72] with MRI reported as a reference standard in seven studies [26, 38, 41, 42, 45, 49, 75].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only two studies [6, 8] were not considered at risk of bias (Table 3). One study was an RCT [6], seven studies had a prospective design [8, 42, 43, 49, 54, 72, 75] and 14 assessed patients retrospectively [9, 12, 18, 20, 22, 26, 33, 38, 39, 41, 44, 45, 57, 62]. Arthroscopy and/or arthrotomy was used as a gold standard in 17 studies [6, 8, 9, 11, 12, 18, 20, 22, 25, 38, 39, 43, 44, 54, 57, 62, 72] with MRI reported as a reference standard in seven studies [26, 38, 41, 42, 45, 49, 75].…”
Section: Resultsmentioning
confidence: 99%
“…Isolated ACL tears were analysed in seven studies [6, 9, 11, 20, 25, 42, 49], whereas ten studies recruited patients with an isolated ACL tear or combined ACL tear and meniscal injury [8, 18, 20, 22, 26, 39, 41, 62, 72, 75]. The spectrum of conditions was not specified or unclear in eight studies [12, 18, 33, 38, 43–45, 57]. Patient cohorts with complete ACL tears only were analysed by ten studies [6, 8, 11, 12, 20, 25, 39, 42, 44, 75], partial ACL tears only were analysed in two studies [22, 42], combined complete and partial ACL tears in nine studies [9, 18, 22, 26, 38, 43, 45, 49, 75].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations